Functional characterisation of murine gammaherpesvirus 68 glycoprotein 150 - Atkin, Isobel Mary Dawber (The University of Edinburgh, 2000)
Murine gammaherpesvirus 68 (MHV-68) is a B cell tropic pathogen of small rodents which shares genetic and pathobiological similarities with Epstein-Barr virus (EBV) and Kaposi's sarcoma associated herpesvirus (KSHV). Unlike EBV and KSHV, MHV-68 replicates well in vitro and infects inbred mice making it a valuable and amenable model for the study of gammaherpesvirus replication and their interaction with the host. Glycoprotein 150 (gpl50) is a virion membrane glycoprotein of MHV-68 that shares similarities with gp340/220 a membrane glycoprotein of EBV which facilitates EBV attachment to B cells. Antibodies against gpl50 have been reported to neutralise MHV-68 infection. The aim of this study was to determine the function of gpl50 and latterly to assess the potential of gpl50 as a vaccine antigen to prime and protect inbred mice against MHV-68 infection. For functional studies of gpl50 two main strategies were adopted; (i) the production of a recombinant virus in which the gene encoding gpl50 is made dysfunctional resulting in a gpl50 'knockout' (KO) virus and (ii) generation and use of purified gpl50 in cell binding studies to determine if gpl50 can bind to cells. Recombinant viruses were generated; virus induced plaques expressing the green fluorescent protein, used as a marker gene for identification of recombinant viruses, were observed. However, no viruses in which the required deletion of the gpl50 gene had occurred were isolated. A gpl50-His fusion protein (gpl50-His) consisting of the extracellular domain of gpl50 attached to a hexahistidine residue was successfully cloned, expressed in bacteria and purified. Similarly, a glutathione-S-transferase-His (GST-His) fusion protein was generated to be used as a control in binding studies. No significant binding of gpl50-His to murine epithelial cells was detected in an enzyme linked immunosorbent assay (ELISA) or by fluorescent associated cell sorting (FACS) analysis. In contrast, significant binding of gpl50-His to primary splenocytes was shown by FACS analysis. Gpl50-His also bound to purified splenic B cells and both CD19+ (B cells) and CD 19" splenocytes. Antibodies against gpl50 failed to block binding of MHV-68 to murine epithelial cells. Results indicate that gpl50-His binds the heterogeneous splenic cell population as a whole i.e. not a particular subset of lymphocytes. This suggests gpl50 may interact with a ubiquitous cell surface protein or perhaps a protein specific to leukocytes and could be involved in MHV-68 attachment to these cells. Gene gun nucleic acid immunisation of inbred mice with a plasmid encoding gpl50 under the control of a constitutive promoter, alone or in combination with a recombinant vaccinia virus expressing gpl50 (VVᵍᵖ¹⁵⁰) was undertaken followed by intranasal challenge with MHV-68. Virus specific antibody appeared earlier in the group that received gpl50 DNA plus VVᵍᵖ¹⁵⁰. The groups that received gpl50 DNA in conjunction with either VVᵍᵖ¹⁵⁰ or a control vaccinia virus (VVgpt) appeared to have reduced levels of latently infected cells in the spleen day 15 post infection and reduced splenomegaly (a phenomenon of MHV-68 infection) in comparison with control mice. This could indicate that vaccinia virus, in a non-specific manner, boosts the specific immune response to previously administered DNA and in this case was able to limit the level of MHV-68 reaching the spleen. However, this vaccine regimen failed to significantly alter the level of infectious virus in the lung or prevent the establishment of latent virus in the spleen.